2017
DOI: 10.5812/semj.55094
|View full text |Cite
|
Sign up to set email alerts
|

The Survey of Magnesium Sulfate in Prevention of Intraventricular Hemorrhage in Premature Infants: A Randomized Clinical Trial

Abstract: Background: Intraventricular hemorrhage (IVH) is a common complication seen in premature infants. Since the brain intraventricular hemorrhage in any degree of risk is an important factor in long-term neuropathology, the role of magnesium sulfate on cerebral hemorrhage requires further investigation. Therefore, this study aimed to investigate the effect of magnesium sulfate on intraventricular hemorrhage in infants of mothers with premature rupture of membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…This comparison included 18 trials. The indication for use of magnesium sulphate in 6 trials was the prevention of eclampsia [30,32,39,43,48,61]; in 6 trials, fetal neuroprotection [28,36,45,47,51,54]; and in 6 trials, the prevention of preterm birth (tocolysis) [3335,38,40,46]. Magnesium sulphate regimens assessed varied considerably: 4-gram IV loading dose only (2 trials), 4-gram IV loading dose and 1-gram-per-hour IV maintenance dose (4 trials), 4-gram IV loading dose and 2-gram-per-hour IV maintenance (4 trials), 6-gram IV loading dose and 2-gram-per-hour IV maintenance dose (6 trials), and 4-gram IV and 10-gram IM loading dose and 5-gram IM maintenance dose every 4 hours (2 trials), with duration of treatment generally ranging from 12 to 24 hours.…”
Section: Resultsmentioning
confidence: 99%
“…This comparison included 18 trials. The indication for use of magnesium sulphate in 6 trials was the prevention of eclampsia [30,32,39,43,48,61]; in 6 trials, fetal neuroprotection [28,36,45,47,51,54]; and in 6 trials, the prevention of preterm birth (tocolysis) [3335,38,40,46]. Magnesium sulphate regimens assessed varied considerably: 4-gram IV loading dose only (2 trials), 4-gram IV loading dose and 1-gram-per-hour IV maintenance dose (4 trials), 4-gram IV loading dose and 2-gram-per-hour IV maintenance (4 trials), 6-gram IV loading dose and 2-gram-per-hour IV maintenance dose (6 trials), and 4-gram IV and 10-gram IM loading dose and 5-gram IM maintenance dose every 4 hours (2 trials), with duration of treatment generally ranging from 12 to 24 hours.…”
Section: Resultsmentioning
confidence: 99%
“…In this systematic review and meta-analysis of 221 trials that assessed 44 perinatal interventions, we found with moderate certainty that antenatal corticosteroids for lung maturation (small decrease) and indomethacin prophylaxis (moderate decrease) were associated with reduced risk of sIVH in preterm neonates. We also found low certainty evidence that volume-targeted ventilation (large decrease), early ESAs (moderate decrease), and prophylactic ethamsylate (moderate decrease) were associated with lower risk of sIVH, whereas UCM (moderate increase) were associated with higher risk of sIVH in preterm neonates.…”
Section: Discussionmentioning
confidence: 93%
“…We further determined the eligibility of 395 short-listed articles and excluded 174 articles for the reasons shown in eAppendix 4 in Supplement 1. A total of 221 RCTs were included in the final sample . These trials evaluated 44 interventions, which included 6 antenatal, 6 delivery room, and 32 neonatal interventions.…”
Section: Resultsmentioning
confidence: 99%
“…Si la paciente cuenta con antecedentes de RPM se debe preparar a la madre para estar atenta frente a signo y síntomas que puedan sugerir la aparición de dicha entidad. Si la paciente ya cuenta con la instauración de la RPM, se debe iniciar antibioticoterapia profiláctica y corticoterapia de ser necesario (38).…”
Section: A6 -Prevenciónunclassified